2014
DOI: 10.1038/nature13603
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of glutamate receptor activation and desensitization

Abstract: Ionotropic glutamate receptors are ligand-gated ion channels that mediate excitatory synaptic transmission in the vertebrate brain. To better understand how structural changes gate ion flux across the membrane, we trapped AMPA and kainate receptor subtypes in their major functional states and analyzed the resulting structures using cryo-electron microscopy. We show that transition to the active state involves a corkscrew motion of the receptor assembly, driven by closure of the ligand binding domain. Desensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
262
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(296 citation statements)
references
References 53 publications
32
262
0
Order By: Relevance
“…Structures of AMPARs captured in various functional states using X-ray crystallography and cryoelectron microscopy have recently become available (5)(6)(7)(8)(9). Overall, the structures confirm three distinct structural layers (Fig.…”
mentioning
confidence: 73%
“…Structures of AMPARs captured in various functional states using X-ray crystallography and cryoelectron microscopy have recently become available (5)(6)(7)(8)(9). Overall, the structures confirm three distinct structural layers (Fig.…”
mentioning
confidence: 73%
“…However, it has been previously shown that reduction of GluD2 LC activity by D-Ser results from conformational changes at the LBD dimer interface (Hansen et al, 2009). Interestingly, conformational changes at the LBD dimer interface reflect desensitization of AMPA and kainate receptors (Armstrong et al, 2006;Plested and Mayer, 2009;Daniels et al, 2013;Schauder et al, 2013;Durr et al, 2014;Meyerson et al, 2014), and the extent of desensitization of AMPA receptors is correlated with the degree of domain closure (Jin and Gouaux, 2003). That is, ligands that induce full domain closure desensitize AMPA receptors to a higher extent than ligands that induce less closure.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first crystal structure for a nearfull-length AMPA receptor in antagonist-bound form was first presented in 2009 (3), more than a dozen such structures covering both AMPA and NMDA receptors have been published (4,(24)(25)(26)(27)(28). Some of these structures are bound with full agonists along with positive allosteric modulators.…”
Section: Introductionmentioning
confidence: 99%